Korelasi Pemahaman Memberi Persembahan Dari Lukas 21:1-4 Terhadap Partisipasi Memberi Jemaat Gereja Sidang Jemaat Allah Desa Pait - Kasembon Malang - Kasiatin Widianto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2017)
Offering made by Christians today cannot be separated from the teachings of the Bible both the Old Testament and the New Testament. Offerings should be offered seriously with full sincerity and an attitude of sacrifice. Giving offerings does not talk about how much material or wealth is given, but talks about sincerity and longing to give the best to God. The discussion of the results of quantitative research proved that the congregation of the Gereja Sidang Jemaat Allah Pait Kasembon Malang understood the doctrine of the meaning of giving offerings in the Gospel of Luke 21: 1-4 for 44.5%, so the congregation would participate in giving offerings with the right motivation and the best quality for God. Thus the results of this study indicate that the result is in accordance with what the researcher has proposed before.